Formation Periods (Evolution) of Traditional Japanese Garden-Park Art - Uralov Akhtam Sindarovich; Boboyeva Fotima Sobirjonovna (American Journal of Biodiversity, 2025)
This article provides a comprehensive and synthesized analysis of the formation process of traditional Japanese garden-park art through the lens of its developmental periods. It examines changes in the characteristics, types, compositional solutions, and structural elements of Japanese gardens during each historical period. Additionally, the factors influencing the formation of traditional Japanese gardens, as well as the functions performed by gardens in each period, are analyzed. The study also considers the impact of political, economic, and religious contexts on garden formation throughout Japan’s history.